A three-phase linear load flow solution based on loop-analysis theory for distribution system. Issue 2 (4th October 2018) - Li, Hong wei; Zhu, Hairong; Pan, Li
Abstract : Purpose: To realize the operation optimizing of today's distribution power system (DPS ), like economic dispatch, contingency analysis, and reliability and security assessment etc., it is beneficial and indispensable that a faster linear load flow method is adopted with a reasonable accuracy. Considering the high R/X branch ratios and unbalanced features of DPS, the purpose of this paper is to propose a faster and non-iterative linear load flow solution for DPS. Design/methodology/approach: Based on complex function theory, the derivations of the injection current linear approximation have been proposed for the balanced and the single-, double- and three-phase unbalanced loads of DPS on complex plane. Then, a simple and direct linear load flow has been developed with loop-analysis theory and node-branch incidence matrix. Findings: The methodology is appropriate for balanced and single-, double- and three-phase hybrid distribution system with different load models. It provides a fast and robust load flow method with a satisfactory accuracy to handle the problems of DPS whenever the load flow solutions are required. Research limitations/implications: The distributed generators (DGs) with unity or fixed power factors can be easily included. But the power and voltage nodes cannot be dealt with directly and need to be further studied. Originality/value: By combining the current linear approximation with the loop theory-based method, a new linear load flow method for DPS has been proposed. The method is valid and acute enough for balanced and unbalanced systems and has no convergent problems.